Analisis Puisi “Aku Membawa Angin” Karya Heri Isnaini Dengan Menggunakan Pendekatan Semiotik - Dedi Soepandi (Asosiasi Periset Bahasa Sastra Indonesia, 2023)
Semiotically, poetry is a systematic and meaningful structure of signs determined by convention. Understanding poetry is nothing other than understanding the meaning of poetry. The meaning of poetry is a work that arises from language which is arranged based on literary structure according to its conventions. Therefore, to study poetry, it is necessary to conduct a semiotic analysis of the land, remembering that poetry is a structure of meaningful signs. The semiotic approach is considered capable of expressing the meaning contained in poetry, so this approach has received a lot of attention, namely with the research that has been produced. This article aims to discuss the hidden meaning of poetic texts through discussion and explanation from a semiotic perspective. This theory is used as a basis for explaining poetry in terms of the signs and interpretations thereof. The method used is descriptive qualitative with a focus on poetry as the object and research data. The results of this research show that the poem